THE ACTUALIZATION OF LEADERHSIP MODELS ADOPTED BY FIELD IMPLEMENTERS IN INFLUENCING THE CONTRACTOR EMPLOYEES’ MOTIVATION AND PERFORMANCE - Irawan, Dafid; Mochtar, Indrasurya B.; Utomo, Christiono (Journal of Applied Engineering Science, 2019)
The quality of foremen, handymen, and workers plays an important role in improving the building quality. In this case, field implementers should not only possess communication ability with their site engineers, site managers, and the workers, but also technical and managerial ability to make a direct relationship with the foremen, skilled handymen or blue-collar workers. From the organizational relationship, field implementers should be able to implement the work drawing with a certain method of implementation in order to create a building by optimizing the available resources. The objective of this present research is to test and analyze the actualization of the leadership model adopted by the field implementers in influencing the contractor employees’ motivation and performance. This research was conducted in Contractors with grades 5, 6, and 7 in Malang, Surabaya, Blitar, and Probolinggo cities. The findings of this present research are as follows: (1) a combinational leadership significantly influenced the employees’ performance; (2) work motivation significantly influenced the improvement of the employees’ performance; (3) task- and person- oriented leadership and liberalization leadership styles indirectly influenced the employees’ performance through motivation. In the three relationships, the leadership position is very important since it would give great changes of employees’ work motivation and performance.